(untitled) (American Journal of Islam and Society, 2014)
Ethical identity refers to the set of guidelines that promote ethical practices within and by the organization. This concept is embedded in the Islamic teaching. This study examines the ethical identity of Islamic banks in Bangladesh, Malaysia, and the Arab Gulf region under eight distinctive dimensions to explore the difference between ideal and communicated ethical conducts via annual reports. This study’s findings reveal an immediate need to develop ethical identity disclosure requirements for Islamic banks. Other areas of special importance include focused social and developmental goals, putting the Shari‘ah strategically in the mission and vision statements, enhanced employee welfare policy, and effective Shari‘ah monitoring of banking operations.